Buen Vivir and the Art of Living: Comparing Western and Latin American Perspectives on Living a “Good Life” - Teschers, Christoph; Nieto, Maria (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2023)
While interaction and exchange between cultures is arguably increasing in our globalized world, sentiments reflecting division among cultures and ways of being in the world remain. In particular, the relevance of ideas, theory, and philosophy based on traditional “Western” values and a focus on the individual is often drawn into question for collectivist and community-centred cultures—and vice versa. This has implications for education, given that much of the education discourse and approaches based on Western traditions are affecting education system across the globe and across cultures. It is also of particular significance for the educational approach focusing on developing students’ own “art of living.” While undoubtedly significant fundamental differences exist between most cultures, this article aims to suggest that, nevertheless, synergies and connecting points exist between Schmid’s philosophical concept of the “art of living”—which is based on so-called traditional Western philosophy—and the Latin American notion of “buen vivir” (good living)—which is based on the traditions and cultural worldview of Indigenous peoples of this subcontinent. While we acknowledge the vast differences in culture and the depths of the cultural divide, our comparative review indicates that connections can be drawn on fundamental ethical aspects of human co-existence. We argue that these connecting points suggest that Schmid’s philosophy can be of relevance to non-Western cultural contexts, as much as Indigenous ways of knowing and being can be of relevance to those in the “Western” world pursuing an art of living, which, consequently, indicates that an educational approach to the art of living can be relevant to diverse cultural contexts beyond Western-centric settings.